2021
DOI: 10.3390/v13122507
|View full text |Cite
|
Sign up to set email alerts
|

Vector Competence of the Invasive Mosquito Species Aedes koreicus for Arboviruses and Interference with a Novel Insect Specific Virus

Abstract: The global spread of invasive mosquito species increases arbovirus infections. In addition to the invasive species Aedes albopictus and Aedes japonicus, Aedes koreicus has spread within Central Europe. Extensive information on its vector competence is missing. Ae. koreicus from Germany were investigated for their vector competence for chikungunya virus (CHIKV), Zika virus (ZIKV) and West Nile virus (WNV). Experiments were performed under different climate conditions (27 ± 5 °C; 24 ± 5 °C) for fourteen days. Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 50 publications
(56 reference statements)
2
27
0
Order By: Relevance
“…The species was subsequently detected in Italy in 2011 (Capelli et al, 2011 ; Marcantonio et al, 2016 ; Ballardini et al, 2019 ; Negri et al, 2021 ), European Russia (Bezzhonova et al, 2014 ), Germany (Werner et al, 2016 ; Pfitzner et al, 2018 ; Zotzmann et al, 2019 ; Hohmeister et al, 2021 ), Swiss–Italian border region (Suter et al, 2015 ), Hungary (Kurucz et al, 2016 ), Slovenia (Kalan et al, 2017 ), Sochi, Russia (Ganushkina et al, 2016 ), Crimea (Kovalenko and Tikhonov, 2019 ; Ganushkina et al, 2020 ), Austria (Fuehrer et al, 2020 ), and Republic of Kazakhstan (Andreeva et al, 2021 ) (see Figure 1 ) for further details). A. koreicus is nowadays established (Jansen et al, 2021 ) in all the countries mentioned above except Slovenia and Switzerland (ECDC, 2020 ). In 2021, the first finding of A. koreicus larvae in the Netherlands was made (Teekema et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The species was subsequently detected in Italy in 2011 (Capelli et al, 2011 ; Marcantonio et al, 2016 ; Ballardini et al, 2019 ; Negri et al, 2021 ), European Russia (Bezzhonova et al, 2014 ), Germany (Werner et al, 2016 ; Pfitzner et al, 2018 ; Zotzmann et al, 2019 ; Hohmeister et al, 2021 ), Swiss–Italian border region (Suter et al, 2015 ), Hungary (Kurucz et al, 2016 ), Slovenia (Kalan et al, 2017 ), Sochi, Russia (Ganushkina et al, 2016 ), Crimea (Kovalenko and Tikhonov, 2019 ; Ganushkina et al, 2020 ), Austria (Fuehrer et al, 2020 ), and Republic of Kazakhstan (Andreeva et al, 2021 ) (see Figure 1 ) for further details). A. koreicus is nowadays established (Jansen et al, 2021 ) in all the countries mentioned above except Slovenia and Switzerland (ECDC, 2020 ). In 2021, the first finding of A. koreicus larvae in the Netherlands was made (Teekema et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this Special Issue, "Mosquito-Borne Virus Ecology", was to compile scientific data on MBVs that are currently of public health importance and the effect of ecological factors influencing the occurrence and transmission risks of these viruses. This Special Issue has some interesting contributions to science in relation to the geographical distribution of MBVs, vector competence, the effect of temperature, and mosquito vector surveillance [1][2][3][4][5][6][7][8][9][10][11]. It includes both original and review articles that provide important contributions to the scientific literature.…”
mentioning
confidence: 99%
“…The distribution of mosquito-associated viruses in West Africa was analyzed, which provides a general overview of mosquito vectors and MBVs recorded in the West African region [3]. Different studies also reported the vector competence of different mosquito vectors for certain MBVs [4,5,[9][10][11]. The competence of a mosquito vector for a particular MBV depends on the intrinsic and extrinsic characteristics of both the vector and the target virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aedes koreicus originates from Korea, Japan, and northeast China and is present in some regions of Austria, Belgium, Germany, Hungary, Italy, Slovenia and the Swiss-Italian border [30][31][32][33][34][35][36][37]. It is not considered a major vector of VBDs, although field evidence suggests it is a potential vector of Japanese encephalitis virus [38], and laboratory trials have showed low-level transmission of chikungunya and Zika viruses [39,40]. Moreover, it is likely to be a competent vector of Dirofilaria immitis [41].…”
Section: Data Description Backgroundmentioning
confidence: 99%